Occurrence of aflatoxin B1 in baby foods marketed in Iran. (29th November 2016) - Mottaghianpour, Ehsan; Nazari, Firouzeh; Mehrasbi, Mohammad Reza; Hosseini, Mir‐Jamal
Abstract: BACKGROUND: Aflatoxin B1 (AFB1 ), a toxic fungal metabolite that is found in baby foods, can lead to serious complications for children's health. In the present study, 48 commercial baby foods available in the Iranian market were investigated for the presence of AFB1 using a high performance liquid chromatography system that was equipped with post‐column photochemical derivatization and a fluorescence detector. RESULTS: Thirty‐three out of 48 samples (68.7%) were contaminated with AFB1 at median, maximum and mean concentration levels of 0.11, 15.15 and 2.602 ± 4.065 µg kg −1, respectively. The AFB1 concentration in 39.6% of the samples was higher than the maximum level established in Iran for AFB1 within baby foods containing milk (0.5 µg kg −1 ). The incidence of AFB1 in rice, wheat and multigrain infant cereal samples was 90%, 25% and 100%, respectively, whereas rice‐based baby foods contained the highest levels of AFB1 . CONCLUSION: In the present study, the finding of both high rates and high levels of AFB1 in cereal baby foods indicates the need to reduce AFB1 contamination in these products. Therefore, further monitoring and control of pre‐ and post‐harvest, storage, and manufacturing processes is required. © 2016 Society of Chemical Industry